Oxidative Stress and Phospholipid Alterations in Destructive Cholecystitis and Cholelithiasis: A Comprehensive Analysis - Tugolbai Tagaev, Arystanbek Atykanov, Taalaibek Bekov (Asian Journal of Pharmaceutics (AJP), 2025)
Oxidative stress, lipid peroxidation (LPO), and antioxidant depletion are crucial in the pathogenesis of destructive cholecystitis and cholelithiasis. Objectives: This study investigated the influence of these factors on the phospholipid (PL) composition of erythrocyte membranes in patients with acute calculous cholecystitis (ACC), chronic calculous cholecystitis, and gangrenous ACC. Methods: Markers of LPO, antioxidant defense, and endogenous intoxication were measured in blood plasma and erythrocyte membranes. The PL fractions in the erythrocyte membranes were analyzed using thin-layer chromatography. Results: The results showed increased levels of diene conjugates and malondialdehyde, indicating significant LPO in destructive cholecystitis cases. Antioxidant defenses were depleted, as evidenced by the decreased total antioxidant activity and catalase levels. Elevated levels of medium-molecular-weight peptides and phospholipase activity indicate systemic inflammatory responses and internal intoxication. Notable changes in the erythrocyte membrane PL composition included increased lysophosphatidylcholine and reduced phosphatidylcholine levels, suggesting membrane degradation. The increased ratio of easily oxidizable PL fractions to less oxidizable fractions indicates membrane instability and oxidative stress. Conclusion: These findings confirm that oxidative stress, PL changes, and weakened antioxidant defense contribute to the progression of destructive cholecystitis and cholelithiasis. Understanding these molecular alterations can help identify novel diagnostic markers and therapeutic targets for biliary tract diseases.